Kompetensi Guru dan Strategi Instruksional dalam Meningkatkan Kualitas Belajar Siswa - Afriansyah, Fadli; Sirajuddin, Sirajuddin; Zulkarnain, Zulkarnain; A. Suradi, A. Suradi (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this research is to find out how the competence and instructional strategies of teachers in improving the quality of student learning. The method used is library research, in the form of literature review of relevant sources from books and research journals. The research results obtained information that teacher competence, pedagogic abilities and teacher motivation to students are components that play an important role in improving the quality of student learning, which ultimately determines the ability of teacher instructional strategies. The conclusion of a teacher's professionalism can be seen in his ability to apply instructional strategies in learning. The more competent and professional a teacher is, the more maximal the instructional strategy will be in an effort to improve the quality of student learning, Keywords: Teacher Competence, Teacher Professionalism, Instructional Strategy